History of mathematics highways and byways - Dahan-Dalmedico, Amy.; Peiffer, Jeanne; Mathematical Association of America ([Washington, D.C.] Mathematical Association of America, 2010)
A translation of the original 1986 French edition by Amy Dahan-Dalmedico and Jeanne Peiffer (both from Centre National de la Recherche Scientifique, Paris), this eminently readable book places the birth and development of mathematical activity in historical, cultural, and economic context. The book offers an outstanding account, for instance, of how Arabs preserved Greek mathematics and extended it over an 800-year period, from 400-1200. The large number of illustrations supports the text and contributes to a fine read. - Publisher.
Landscapes -- A moment of rationality : Greece -- The constitution of classical algebra -- Figures, spaces, and geometries -- Limits : from initial thoughts to the concept -- The concept of function and the development of analysis -- At the crossroads of algebra, analysis, and geometry : complex numbers -- New objects. New laws. The emergence of algebraic structures.
Includes bibliographical references (p. 327) and index.
Translated from the French.
Keywords: Mathematics -- History